THE ROLE OF COMPETENCY ON SERVICE DELIVERY - Alier, Dr. Gabriel; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
The study aimed at establish relationship between competence and service delivery; and to study or determine factors structure between competence and service delivery. The study findings show that the majority of the employees in Jubek state agreed that their performance is influenced by motivation. The more motivated employees to work, the better the quality service delivery, Thus, the motivation needs to be maintained and enhanced, for example, through awards, appreciation of the work done, training capacity building, good working environment as well as promotions and growth in the company. The study also confirms and supports several previous studies that employee competence has a significant and positive effect on service delivery. The better the competency of the employees, the better the quality of the services provided. According to the staff in Jubek state, employee competence with the indicators of understanding the regulations, technical procedure, duties, and responsibilities will significantly affect the reliability of the employees to provide technical service, to answer customer inquiries and to response complaints. A good competence employee will provide a good service. A qualified service can be delivered to the maximum if the employee has a good competence in their field.